Oxidative stress, antioxidants and hypertension - Amponsah-Offeh, Michael; Diaba-Nuhoho, Patrick; Speier, Stephan; Morawietz, Henning (Antioxidants, 2023)
As a major cause of morbidity and mortality globally, hypertension remains a serious threat to global public health. Despite the availability of many antihypertensive medications, several hypertensive individuals are resistant to standard treatments, and are unable to control their blood pressure. Regulation of the renin-angiotensin-aldosterone system (RAAS) controlling blood pressure, activation of the immune system triggering inflammation and production of reactive oxygen species, leading to oxidative stress and redox-sensitive signaling, have been implicated in the pathogenesis of hypertension. Thus, besides standard antihypertensive medications, which lower arterial pressure, antioxidant medications were tested to improve antihypertensive treatment. We review and discuss the role of oxidative stress in the pathophysiology of hypertension and the potential use of antioxidants in the management of hypertension and its associated organ damage.
Gesehen am 16.05.2024